Efficient Production of Scleroglucan by Sclerotium rolfsii and Insights Into Molecular Weight Modification by High-Pressure Homogenization - Zeng, Weizhu; Wang, Junyi; Shan, Xiaoyu; Yu, Shiqin; Zhou, Jingwen (Frontiers in Bioengineering and Biotechnology, 2021)
Scleroglucan is a non-ionic water-soluble polysaccharide, and has been widely used in the petroleum, food, medicine and cosmetics industries. Currently, scleroglucan is mainly produced by Sclerotium rolfsii. A higher level of scleroglucan (42.0 g/L) was previously obtained with S. rolfsii WSH-G01. However, the production of scleroglucan was reduced despite a higher glucose concentration remaining. Additionally, the molecular weight of scleroglucan was large, thus restricted its application. In this study, by adjusting the state of seeds inoculated, the degradation issue of scleroglucan during the fermentation process was solved. By comparing different fed-batch strategies, 66.6 g/L of scleroglucan was harvested by a two-dose fed-batch mode, with 53.3% glucose conversion ratio. To modify the molecular weight of scleroglucan, a combination method with HCl and high-pressure homogenization treatment was established. Finally, scleroglucan with molecular weight of 4.61×10^5 Da was obtained. The developed approaches provide references for the biosynthesis and molecular weight modification of polysaccharides.